The Investigation of Stefan Luchian Heritage Paintings—A Multi-Analytical Approach - Andrei Victor Oancea; Bogdana Simionescu; Laura Elena Ursu; Mioara Murariu; Marius Dobromir; Maria Geba; Lacramioara Stratulat; Mihaela Olaru (Heritage)
Based on a multi-analytical approach involving mobile techniques and lab-based devices (XPS, portable and micro-Raman spectroscopies, and ATR-FTIR spectroscopy, combined with SEM/EDS and optical microscopy), this study presents the first in-depth investigation of two cultural heritage artworks painted by the famous Romanian artist Ștefan Luchian. The research highlights the artist’s use of a wide range of colors, with his palette including classic pigments such as ochers, lead white, barium white, zinc white, and viridian, as well as contemporary colors such as cobalt purple, alizarin crimson, and the little-known indium yellow. Additionally, attempts are made to characterize the binders used in the paintings, which include linseed oil and animal glue. Beyond identifying the types of pigments and materials used by the artist and assessing the degradation stage of the paintings, this study is the first to provide information regarding the use of In2O3 as a yellow pigment in artwork.